Coworker Support: A Systematic Literature Review - Amalia Dhiaz Fadhira; Joko Suyono (Jurnal Syntax Transformation, 2024)
The emergence of coworker support has become a hot topic of debate in academic circles because it has an impact on job satisfaction, performance improvement, and reduces employee desire to resign. This research uses systematic literature review with the aim of providing an overview of the development of the topic through the latest data and providing suggestions for future research development. The literature taken over the last ten years since 2013 was processed using the Watase UAKE application to obtain article extraction in the form of article information, the theory underlying the article, to future research opportunities. The results show that 2022 is the year with the most relevant articles, the International Journal of Hospitality Management as the most cited or cited journal, and China as the country with the most publications. Of the 27 articles extracted, resource conservation theory is the theory most widely used as a basis for research.